Breakup of rectangular liquid jets with controlled upstream disturbances. (June 2021) - Zhang, Mengsen; Zhu, Jianqin; Tao, Zhi; Qiu, Lu
Highlights: Breakup characteristics of rectangular jets are experimentally investigated. A better characteristic length for rectangular nozzles is developed. Boundaries of orderly breakup for rectangular jets are determined. Roadmap is developed for generating a droplet stream with desired parameters. Abstract: The breakup characteristics of micro rectangular jets with external disturbances were experimentally investigated. The hydraulic diameter of the orifice changed from 0.1 mm to 0.4 mm, whereas the aspect ratio of the cross section varied from 10 to 30. The external disturbance was generated by the piezoelectric ceramic, which was excited by a function generator with a frequency from 0 kHz to 15 kHz. The results showed that the evolution of the ejected rectangular jet experienced three stages from the nozzle to the downstream locations, namely, the axis-switching rectangular jet, the disturbance induced jet fluctuation, and the structured droplet train after the breakup. The time period of the axis-switching wave was independent of jet Weber number. The axis-switching jet could breakup into orderly droplet train, equally spaced droplet stream with same droplet size, when the jet velocity and disturbance frequency felled in a specific region for a given nozzle. In order to generate a droplet train with desired droplet size and frequency in some applications, the nozzle size and jet velocity should be carefully selected. Moreover, it was found that the area-based equivalence diameter was better than the hydraulic diameter as the characteristic length for rectangular jets.